HUBUNGAN PERSEPSI GURU, KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM SEKOLAH DENGAN KOMPETENSI PEDAGOGIK - Sulistiyati Sulistiyati; Sowiyah Sowiyah; Riswanti Rini (9 772338317006)
The purpose of this research is to analyze and know the relations between: (1) leadership of principal with pedagogic competency of teacher, (2) school climate with pedagogic competency of teacher, (3) leadership of headmaster and school climate simultaneously with pedagogic competency of teacher on elementary. The kind of this research is quantitative by using method of expost facto. Data are obtained from questionnaire and documentation, and then analyzed by used correlation technique and regression both simple and double. Hypothesis test is done by Product Moment correlation, which have been done before with analyze precondition test. The results of this research are, (1) the teacher should be able to increase his/her pedagogic competency and are not satisfied with the performance that has been achieved, so it can cause optimal school climate, (2) The principals should give more attention in case of Teachers performance so it can increase school climate.Tujuan dari penelitian ini adalah untuk menganalisis dan mengetahui hubungan antara: (1) kepemimpinan kepala dengan kompetensi pedagogik guru, (2) iklim sekolah dengan kompetensi pedagogik guru, (3) kepemimpinan kepala sekolah dan iklim sekolah bersamaan dengan kompetensi pedagogik guru di SD. Jenis penelitian ini adalah kuantitatif dengan menggunakan metode expost facto. Data diperoleh dari kuesioner dan dokumentasi, kemudian dianalisis dengan teknik korelasi dan regresi yang digunakan sederhana dan ganda. Uji hipotesis dilakukan dengan korelasi Product Moment, yang telah dilakukan sebelumnya dengan analisis uji prasyarat. Hasil penelitian ini adalah, (1) guru harus mampu meningkatkan / kompetensi pedagogik nya dan tidak puas dengan kinerja yang telah dicapai, sehingga dapat menyebabkan iklim sekolah yang optimal, (2) Kepala sekolah harus memberikan lebih perhatian dalam hal kinerja guru sehingga dapat meningkatkan iklim sekolah.Kata kunci: kepemimpinan kepala sekolah, iklim sekolah, kompetensi paedagogik guru